Impact of tqm practices on role stressors: a comparison between middle-leveland operational- level managers in the sri lankan apparel sector - Maldeniya, S.; Kuruppuarachchi, D. (University of Jaffna, 2016)
This study examines the impact of TQM practices on employee role stressors in the Sri Lankan apparel sector. We compare this relationship between two groups namely, middle-level and operational level managers. We collect data from 81 randomly selected respondents including 22 operational-level and 59 middle-level managers. Our sample represents 11 multinational organizations belong to the Sri Lankan apparel industry. We measure TQM practices based on well-established literature covering nine dimensions namely, leadership, customer focus, supplier management, strategic planning, process planning, employee empowerment, training, employee involvement, and teamwork. Role stresses are measured using well known three dimensions in role theory namely, role conflict, role ambiguity, and role overload. We adopt generalized linear models with log Gaussian and log Gamma link functions to investigate the relationships. We identify that role conflict in middle-level managers is influenced by TQM practices but not in operational-level managers. For operational-level managers, role ambiguity and role overload are influenced by TQM practices more than that of the middle-level managers. Role conflicts are negatively related with process management, empowerment, involvement, and supplier focus dimensions of TQM practices while training and customer focus are positively related for middle-level managers. For operational level managers, empowerment reduces the level of role ambiguity while leadership and training tend to increase the same. Only teamwork affects on role ambiguity for middle-level managers. Moreover, supplier management, strategic planning, empowerment, and training increase role overload in operational-level managers. Leadership commitment and employee involvement reduce role overload in both operational-level and middle-level managers.
Keywords: Role conflict; Role ambiguity; Role overload; Sri Lankan Apparel Industry,; Total quality management